Can obesity impact mesh exposure rate after mid-urethral sling operation? Medium term follow-up. (January 2023) - Daykan, Yair; Klein, Zvi; Eliner, Or; O'Reilly, Barry A; Yagur, Yael; Belkin, Shir; Ribak, Rachel; Arbib, Nissim; Schonman, Ron
Abstract: Objective: To study mesh exposure rates among obese (BMI ≥ 30 kg/m 2 ) vs non-obese women after mid-urethral sling (MUS) operation. Study design: This retrospective cohort study included all patients who underwent MUS surgery for stress urinary incontinence April 2014–April 2021 in a tertiary-level university hospital. Data from obese and non-obese patients were compared. Results: A total of 120 (41 %) obese patients and 172 (59 %) non-obese patients who had mid-urethral sling surgery were compared. Of the cohort, 265 (90.7 %) underwent TVT-obturator, 15 (5.1 %) mini-sling TVT, and 12 (4.1 %) retro-pubic TVT. Diabetes mellitus was significantly more prevalent in the obese group (p =.01), without other demographic differences. Mesh post-operative exposure rate was 5.4 % during the study. The obese group had lower incidence of mesh exposure than the non-obese group (1.6 % vs 8.1 % respectively, p =.018). Mean follow-up was 51 months (range 8–87 months) without significant differences between groups (49.9 ± 21.2 vs 51.5 ± 22.3, p =.548). Pelvic organ prolapse, cystocele, and rectocele stages were significantly higher in non-obese patients. Similar numbers of post-menopausal women were in each group. Conclusion: This follow-up after MUS surgery showed an association between obesity and lower rate of mesh exposure. Further research is needed to evaluate correlations between estrogen and mesh exposure.